THE BEHAVIORAL ROLE OF MALES OF PLATYPUS QUERCIVORUS MURAYAMA IN THEIR SUBSOCIAL COLONIES - Hagus Tarno; Hongye Qi; Michimasa Yamasaki; Masahide Kobayashi; Kazuyoshi Futai (AGRIVITA, Journal of Agricultural Science, 2016)
The behavioral role of male ambrosia beetles, Platypus quercivorus, in subsocial colonies both field and laboratory has been investigated. The entrance tunnels, where the male beetles are staying, are short, with a mean 4 cm long and mostly incline upwards from outside to inside at an angle of around 20º. To examine the role of males, another male or female (as the invader) was placed into a tunnel. When inhabitant males stayed in the tunnel they quickly expelled the invaders, regardless of their sex of the invaders. However, when an inhabitant male was removed an introduced male or female could freely enter the tunnel and was accepted by the inhabitant female. Upon replacing an inhabitant male with an invader male or female and then putting another invader male or female into the tunnel, no rejection occurred, suggesting that invader males and females play no role in guarding the tunnel. Based on the results an inhabitant male seems to have three responsibilities; protection of the gallery from invaders, protection of progeny (larva) from falling down and also keeping the gallery clean from frass. The 20º angle of the entrance tunnel tends to aid both in gallery protection and in frass clearing.